The Effect Of Balance Training Of 200-M Kayaking Athlete Performance - Iwan Hermawan; Haris Nugroho; Puspo Nagati Paramita Namira Khanza; Hardiyanti Putri Ning Gusti; Nurhidayat Nurhidayat (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to find out the impact of balance exercises on the achievements of kayaking athletes 200  meters. The method used in this study is a survey using correlational. The sample selected was by criteria of the number of kayakers participating in the National Training Center for rowing in 2019, as many as 28 male athletes. Data analysis using a simple correlation with a significant level of 0.05, overall analysis of this data uses the help of SPSS program version 20.00. The finding is that the R Square value (determination coefficient) is 0.712, which means 71.2% of the total performance variation of 200m kayakers is caused by a simple correlate relationship with variable balance. This means that 71.2% of balance data has a direct influence on the performance of kayakers 200m in 2019 and the remaining 28.8% or (100% - 71.2% = 28.8%) caused by other factors such as weather conditions, mental condition, boat conditions, nutrition, recovery, athlete health conditions, and others